Relations of the Preposition in Motion Verb of the Malay Language Based on Conceptual Structure Representation with Spatial Representation: (Hubungan Preposisi dalam Gerak Ruang Bahasa Melayu Berdasarkan Representasi Struktur Konseptual dengan Representasi Ruang) (Jurnal Bahasa, 2019)
Motion is a change from one location to another location. The typology of motion requires the prepositions as indicators and main components to express the direction of motion. Consequently, this study focuses on spatial motion and prepositions that are present simultaneously such as dari, daripada, ke, kepada, di, di seberang, di sekitar, di sekeliling and di sepanjang, by focusing on conceptual (abstract) structure perspective. This research uses data acquired from the database of Dewan Bahasa dan Pustaka, Malaysia as material and sample of study. Conceptual Structure Theory (CST) (Jackendoff 1997 & 2011) was used to analyse the data. The argument is arranged according to three main hierarchies: argument-adjunct rules, conceptual structure representation and spatial representation. The findings reveal the existence of directional spatial motion, additive motion, becoming motion and orientative motion in function of [EVENT] and [STATE] that can predict the existence of prepositions such as dari, daripada, ke, kepada, di, di seberang, di sekitar, di sekeliling and di sepanjang in bound direction, directive direction and path direction. Spatial representation also demonstrates the involvement of dimension conceptualization such as DIM 0D, DIM 2 (0+E) DIR and DIM 2 (0+E) DIR. Overall, this study shows the relationship of motion and prepositions in conceptual structure representation with spatial representation.Keywords: Motion, preposition, argument-adjung, conseptual, spatial